INTRA-TEXTUAL MEANINGFUL RELATIONS OF PREPOSITIONS IN ITALIAN - Kuranda, Vitalina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article deals with the study of intratextual semantic relations of prepositions in the Italian language. Prepositions are one of the most difficult topics to understand and study. In the Italian language, there is a lot of material that reveals the meaning and use of prepositions. But there are not many classifications that would fully, in a structured form, reveal the relationship of prepositions in a sentence, a fixed expression and in certain constructions. The article collects definitions of the concept of a preposition from both domestic and Italian researchers. Therefore, prepositions should be understood as an invariable part of speech that can accompany a noun, pronoun, adverb or verb in the infinitive, which has many different meanings. Taking the classification of A. Zagnitko as a basis, the article provides a classification of intratextual semantic relations expressed by Italian primary prepositions. Based on this classification, the following relations were distinguished: locational, temporal, possessive, limiting, modal, deliberative, motivational and distributive. This classification contributes to a better understanding of prepositional relations and their meaning in sentences, fixed expressions and various constructions. ______________ References: • Aleksienko, L. A. (2014). Morfologiya suchasnoyi ukrayinskoyi movy: navch. posibnyk [Morphology of the modern Ukrainian language: A textbook]. Kyiv. • Vykhovanets, I. R. (1988). Chastyny movy v semantyko-hramatychnomu aspekti [Parts of speech in the semantic-grammatical aspect]. Kyiv: Naukova Dumka. • Zhovtobryukh, M. A. (1972). Kurs suchasnoyi ukrayinskoyi literaturnoyi movy [Course of the modern Ukrainian literary language]. Kyiv: Vyscha Shkola. • Zagnitko, A. P. (2007). Pryimennnyky u strukturi tekstu: pervynni i vtoronni vyyavy [Prepositions in the structure of the text: Primary and secondary manifestations]. Donetsk: DonNU, 120–131. • Zagnitko, A. P. (2018). Movnosotsiumnyy prostir pryimennyka: dyskursyvni praktyky [Speech-sociological space of the preposition: Discursive practices]. Linhvistychnyi Studii [Linguistic Studies], (35), 14-39. Retrieved from http://nbuv.gov.ua/UJRN/lingst_2018_35_4 • Nocchi, S., & Tartaglione, R. (2006). Grammatica avanzata della lingua italiana [Advanced grammar of the Italian language]. Firenze: Alma Edizioni.